Analysis of the directions of development of regulatory and methodological support for testing agricultural machinery in the Russian Federation - Podolskaya E. E.; Ivanov A. B.; Tarkivsky V. E.; Bondarenko E. V. (E3S Web of Conferences)
The article analyzes current trends and modern approaches to regulatory and methodological support and regulation of testing of agricultural machinery and equipment in the Russian Federation. A general description of the national standardization system for testing and conformity assessment of agricultural machinery is provided. The main areas of development of regulatory and methodological support for testing of agricultural machinery in the Russian Federation are identified and summarized. The requirements for updating regulatory documents related to the development of technologies and market requirements are considered. The best practices in applying new testing methods and tools are summarized. The problems are identified and ways to improve the efficiency of processes and the reliability of results in the field of testing and conformity assessment of agricultural machinery are proposed. The need for compliance of national documents in the field of standardization of testing and conformity assessment with current international requirements is substantiated.